True Median Cleft Lip—15 Years of Review and Prevalence. (August 2020) - Hamzan, Muhammad Izzuddin; Sulaiman, Wan Azman Wan
Objectives: The author presents 4 cases and attempts to analyze the prevalence of true median cleft lip (MCL) in one center. Embryology, associated anomalies, and surgical treatment are discussed. Design: A retrospective descriptive study. Setting: Hospital Universiti Sains Malaysia. Participants: All patients with congenital facial cleft deformities from 2005 to 2019 were retrieved from the Plastic Surgery OR Registry. All characteristics in interest were individually tabulated and evaluated. Four cases were reviewed and discussed. Outcome: Prevalence of true MCL. Results: Out of the 494 patients included in the study, only 4 (0.81%) were affected with a median cleft, and the prevalence of true median cleft was hence determined to be 3 (0.61%) among the cleft population. Conclusion: The prevalence of the true MCL is rare which makes it hard to categorize these clefts, and the surgical protocol needs to be established for the definitive treatment.